2022
DOI: 10.1088/1755-1315/1117/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Selected Mechanical and Physical Properties Concrete with Polypropylene Plastic Granule Aggregate

Abstract: Amount of plastic use contribute significantly to the accumulation of plastic waste. The use of plastic waste in concrete is one of the world’s partial solutions for dealing with plastic waste. Polypropylene plastic granules are used as a partial replacement for fine aggregate in this study. The purpose of this research is to examine the physical and mechanical properties of the chosen base concrete while considering the potential of polypropylene plastic granules as a sand substitute in the concrete mixture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The highest compressive strength was achieved when adding 4% plastic, and the compressive strength decreased significantly when adding 8% and 10% plastic. Sofyan et al [12] performed sand substitution with plastic pellets with 10%, 20%, 30%, and 40% variations. The results showed that the compressive strength of concrete with plastic mixtures decreased by 56.06% compared to the control sample (0% plastic).…”
Section: Introductionmentioning
confidence: 99%
“…The highest compressive strength was achieved when adding 4% plastic, and the compressive strength decreased significantly when adding 8% and 10% plastic. Sofyan et al [12] performed sand substitution with plastic pellets with 10%, 20%, 30%, and 40% variations. The results showed that the compressive strength of concrete with plastic mixtures decreased by 56.06% compared to the control sample (0% plastic).…”
Section: Introductionmentioning
confidence: 99%